Effects of dietary supplementation with quercetagetin on nutrient digestibility, intestinal morphology, immunity, and antioxidant capacity of broilers - Wu, Fengyang; Wang, Haonan; Li, Shuo; Wei, Zhonghua; Han, Shuaijuan; Chen, Baojiang (Frontiers in Veterinary Science, 2022)
Quercetagetin (QG) is gaining increased attention as a potential alternative to in-feed antioxidants due to its antioxidant activity. This experiment was conducted to investigate the effects of dietary supplementation with QG on nutrient digestibility, intestinal morphology, immunity, and antioxidant capacity of broilers. Four hundred 1-day-old Ross 308 broilers were randomly assigned into 4 groups with 10 replicates in each group and 10 broilers in each replicate. The four dietary treatments included the basal diet supplemented with 0, 3.2, 4.8, or 6.4 mg/kg QG. The results showed that dietary supplementation with QG significantly promoted the broilers’ apparent digestibility of phosphorus (P < 0.05), increased the villus height in jejunum and ileum, and reduced the crypt depth in jejunum and ileum, which significantly increased the ratio of villus height to crypt depth in the jejunum and ileum (P < 0.05). The dietary supplementation with QG also significantly enhanced the immunoglobulin G (IgG) and complement 4 (C4) levels in the blood (P < 0.05), the activity of total antioxidant capacity (T-AOC) in serum, jejunum mucosa, and ileum mucosa, the activity of superoxide dismutase (SOD) in the serum and liver (P < 0.05), and significantly up-regulated the kelch-like ECH-associated protein 1 (Keap1), nuclear factor E2 related factor 2 (Nrf2), heme oxygenase-1 (HO-1), NAD(P)H: quinone oxidoreductase 1 (NQO-1), glutathione peroxidase (GSH-Px) and superoxide dismutase 1 (SOD1) mRNA expression levels in the jejunum mucosa, ileum mucosa, and liver tissues of broilers. Therefore, supplementing broilers’ diets with QG can enhance the apparent digestibility of phosphorus, improve the structure and morphology of jejunum and ileum, promote immunity, and increase the activity of antioxidant enzymes and the antioxidantive capacity through the Nrf2 / antioxidant response element (ARE) signaling pathway mediated by Keap1.